The Cranebrook Terrace revisited: recent excavations of an early Holocene alluvial deposit on the banks of the Nepean River, NSW, and their implications for future work in the region. Issue 3 (2nd September 2017) - Williams, Alan N.; Burrow, Adrian; Toms, Phil S.; Brown, Oliver; Richards, Michelle; Bryant, Tessa
Abstract: We present the results of a compliance-based excavation on the banks of Peach Tree Creek within the alluvial margin of the Nepean River, Penrith, NSW. The excavations consisted of (i) two mechanically excavated trenches (3 × 1 m) in controlled 20 cm spits to depths of 4 m below surface, and (ii) a subsequent stage of manual salvage excavation (6 m 2 ) focussing on the artefact-bearing levels indicated by the testing phase. The excavations identified two sedimentary deposits, with the lowest being part of the Cranebrook Formation, a deep alluvial deposit within which artefacts dating to >40 ka have been previously reported. We recovered four indurated mudstone/tuff and two coarse silcrete artefacts, all having characteristics of the late Pleistocene/early Holocene, and which we have OSL dated to >9.5 ka from the upper portion of the Richmond Unit of the Cranebrook Formation (3.5–3.9 m below the surface). Along with a greater understanding of the formation (only a part of which was deposited during the last 50 ka) and recent archaeological discoveries, our results lend increasing support for visitation of the Nepean river corridor by Aboriginal people as a part of the initial colonisation of Australia. It remained a key locale for occupation and visitation throughout the late Pleistocene. Finally, we discuss the current NSW State government guidelines for investigating archaeological deposits and identify concerns about their effectiveness and applicability when investigating areas of potentially deep stratigraphy along the banks of the Nepean River.